It's beginning to look a lot like murder - DiRico, Maria, 1956- (DiRico, Maria, 1956- Catering hall mystery., 2021)
"Mia's busy with a full schedule of events at the family business--among them an over-the-top Nativity-themed first birthday party and a Sweet Sixteen for a teen drama queen. But her personal life is even more challenging. Her estranged mother has returned--and her lifelong friend Jamie has discovered a shocking secret about his past. He's so angry that he starts hanging out with Lorenzo, who claims to be his long-lost brother--even after it becomes clear that Lorenzo's story is as fake as a plastic Christmas tree. Then a body turns up among the elves in a Santa's-workshop lawn display, and amateur sleuth Mia has a buffet of suspects to choose from. Amid the holiday celebrations, she intends to find out who's the guilty party."--